Karakteristik & Diagnosis Keperawatan Pasien Covid-19: Studi Dokumentasi - Juhdeliena, Juhdeliena; Pangkey, Ballsy Cicilia Albertina; Hutasoit, Elissa Oktoviani; Hutasoit, Exadina Romaito (MAHESA : Malahayati Health Student Journal, 2023)
ABSTRACT Health workers are at the forefront of health services needed for suspected and confirmed COVID-19 patients. Nurses have considerable control over conducting initial examinations of patients. The initial examination is carried out by nurses as part of the nursing process. Knowing the characteristics of COVID-19 patients who are treated will help nurses formulate nursing diagnoses, intervene, and evaluate.  Analyze patient characteristics and nursing diagnoses of COVID-19 patients. The research design was descriptive-quantitative with a retrospective documentation study approach. The sample amounted to 40 medical record documents. The results of this study found that cough (75%) was the main symptom complained of by COVID-19 patients, with the average age of COVID-19 patients treated being 48.13 years, the mean systolic blood pressure being 132.25 mmHg, the mean diastolic blood pressure being 81.03 mmHg, the mean temperature at initial admission being 36.6 oC, and the mean length of stay being 13.1 days. The nursing diagnosis most often raised in patients with COVID-19 is airway clearance ineffectiveness (45%). There were 18 characteristics of COVID-19 patients obtained during the initial assessment, and seven nursing diagnoses were raised when the patient was hospitalized. Keywords: Nursing Diagnosis, COVID-19 Patient Characteristics, COVID-19 Pandemic  ABSTRAK Tenaga Kesehatan menjadi lini garis terdepan pelayanan kesehatan yang dibutuhkan pada pasien suspek maupun terkonfirmasi COVID-19. Perawat memegang kendali yang cukup besar dalam melakukan pemeriksaan awal pada pasien. Pemeriksaan awal yang dilakukan oleh perawat sebagai bagian dari proses keperawatan. Dengan mengetahui karakteristik pasien COVID-19 yang dirawat maka akan membantu perawat untuk merumuskan diagnosis keperawatan, melakukan intervensi dan evaluasi. Menganalisis karakteristik pasien dan diagnosis keperawatan pasien COVID-19. Desain penelitian yang digunakan adalah deskriptif kuantitatif dengan pendekatan studi dokumentasi retrospektif. Sampel berjumlah 40 dokumen rekam medis. Hasil penelitian ini didapatkan batuk (75%) menjadi gejala utama yang dikeluhkan oleh pasien COVID-19, dengan rerata usia pasien Covid- 19 yang dirawat adalah 48,13 tahun, rerata tekanan darah sistolik 132,25 mmHg, rerata tekanan darah diastolic 81,03 mmHg, rerata suhu saat awal masuk 36,6oC, rerata lama rawat 13,1 hari. Untuk diagnosis keperawatan yang paling sering diangkat pada pasien dengan COVID-19 adalah ketidakefektifan bersihan jalan napas (45%). Terdapat 18 karakteristik pasien COVID-19 yang didapatkan saat pengkajian awal, dan tujuh diagnosis keperawatan yang diangkat saat pasien menjalani rawat inap. Kata Kunci: Diagnosis Keperawatan, Karakteristik Pasien COVID-19, Pandemi COVID-19